2016
DOI: 10.1016/j.jaci.2016.01.056
|View full text |Cite
|
Sign up to set email alerts
|

Epigenome-wide association study links site-specific DNA methylation changes with cow's milk allergy

Abstract: Summary We demonstrates that DNA methylation alterations at multiple genes, including those in the TH1-TH2 pathways and some novel genes, are associated with cow's milk allergy (CMA), which shed new light on the epigenetic underpinnings of CMA.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
54
0
2

Year Published

2017
2017
2019
2019

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 58 publications
(56 citation statements)
references
References 27 publications
0
54
0
2
Order By: Relevance
“… used blood mononuclear cells obtained from individuals undergoing oral food challenge and found a DNAm signature of 96 CpG sites that predicted oral food challenge outcomes with increased predictability compared with SPTs and sIgE. An epigenome‐wide association study of cow's milk allergy in a subset of children from the Chicago Food Allergy Study and from the Boston Birth Cohort indicates that specific gene loci are associated with cow's milk allergy . Another study found that tolerance in children with IgE‐mediated cow's milk allergy was characterized by a distinct Th1 (IL‐10 and INF‐γ) and Th2 (IL‐4 and IL‐5) cytokine gene DNA methylation pattern .…”
Section: Precision Medicine In Food Allergymentioning
confidence: 99%
“… used blood mononuclear cells obtained from individuals undergoing oral food challenge and found a DNAm signature of 96 CpG sites that predicted oral food challenge outcomes with increased predictability compared with SPTs and sIgE. An epigenome‐wide association study of cow's milk allergy in a subset of children from the Chicago Food Allergy Study and from the Boston Birth Cohort indicates that specific gene loci are associated with cow's milk allergy . Another study found that tolerance in children with IgE‐mediated cow's milk allergy was characterized by a distinct Th1 (IL‐10 and INF‐γ) and Th2 (IL‐4 and IL‐5) cytokine gene DNA methylation pattern .…”
Section: Precision Medicine In Food Allergymentioning
confidence: 99%
“…Several allergy‐related genes, including those related to T‐effector pathways, namely IFN‐γ and IL‐4, have been found to be susceptible to epigenetic regulation . An epigenome‐wide association study in children with CMA revealed alterations of methylation status in Th1‐Th2 response mediator genes (i.e., IL‐1RL1, IL‐5RA, IL‐4, CCL18 and STAT4) in whole‐blood DNA, and their association with the disease . We demonstrated that epigenetic mechanisms, involving DNA methylation of the promoter region of the type 1 helper (Th1) and Th2 cytokine genes and Treg‐specific demethylated region of FoxP3, play a role in tuning the CMA disease course and that dietary strategies could influence these mechanisms differentially .…”
Section: Introductionmentioning
confidence: 81%
“…21 The first epigenome-wide association study of CM allergy in US children identified significant differentially methylated regions in specific gene loci, including genes involved in T H 1-T H 2 regulation and cellular signaling. 22 Although further study is needed, identification of genetic and epigenetic alterations associated with food allergy is important to advance our understanding of the geneenvironment interactions that underlie the development of food allergy.…”
Section: Etiology (Systems Biology/genetics/ Microbiome)mentioning
confidence: 99%
“…Component-resolved analysis of IgA, IgE, and IgG 4 responses during egg OIT identified predictors associated with SU, including EW-specific IgG 4 , IgA, and IgA 2 , with lower pretreatment EW sIgE and ovomucoid sIgE associated with SU. 90 In a retrospective analysis of natural tolerance acquisition to CM, IgE and IgG 4 binding to sequential epitopes of 5 major CM proteins were measured by using a peptide microarray-based immunoassay in sera from 35 children with milk allergy (22 were CM tolerant at a median age of 51 months). 91 Children who acquired natural tolerance to CM had IgE and IgG 4 antibodies that more often recognized the same epitopes, and when evaluated from baseline until the time of tolerance development, both IgE and IgG 4 binding intensity decreased significantly.…”
Section: Mechanisms Of Food Allergy and Immunotherapymentioning
confidence: 99%